Synthesis and Biological Evolution of Some Heterocyclic Derivatives - Zena Ayad Noori; Tabarak Ali Hussein Mahdi; Walid Khaled Obaid; Rusul Abather Mohsen; Safaa Kamel Abdul Razzaq Ali; Russul Jaleel Hassan (Zien Journals, 2023)
Heterocyclic compounds, owing to their diverse applications including pharmaceuticals and industrial use, hold a prominent position within organic chemistry. This study focused on the synthesis and characterization of Schiff base compounds as a subset of heterocyclic molecules. Compound [N1] was synthesized by condensing 3,4 Diamino benzoic acid and 4-Dimethyl amino benzaldehyde, followed by subsequent reactions to yield compounds [N2], [N3], [N4], and [N5]. Each compound was characterized through Fourier-transform infrared spectroscopy (FTIR). The FTIR spectra exhibited distinctive absorption bands signifying various functional groups within each compound. The spectra confirmed the presence of key bonds such as OH, C=O, C=N, C-H, and S-H within the compounds. This thorough characterization validated the successful synthesis of the Schiff base compounds and facilitated their structural analysis. The study underscores the importance of precise characterization in elucidating the structure and composition of novel compounds, contributing to the broader understanding of their potential applications.
Keywords: Heterocyclic Derivatives; Synthesis; Schiff Base Compounds; Fourier-Transform Infrared Spectroscopy (FTIR)